My kind of Christmas - Dailey, Janet (Kensington Books, 2018)
Travis Morgan is not crazy about moving back to Branding Iron, Texas, to run an abandoned ranch he inherited, until he meets the town's sweetly stubborn mayor, Maggie Delaney.
Sometimes the best surprises are right at home ... Returning to Branding Iron, Texas, is Travis Morgan's last resort, and the abandoned ranch he inherited isn't much more welcoming than the prison cell where he spent the last three years doing time for a tragic accident. Completely without funds or family, Travis finds celebrating Christmas is the last thing on his mind, but there's no escaping the holiday spirit in this close-knit little town-not with Branding Iron$1 (Bs longtime Santa retiring, and sweetly stubborn Mayor Maggie Delaney determined to find a replacement. When her no-nonsense facade slips to reveal the sensual, vulnerable woman beneath it, Travis realizes Maggie just might be as lonely as he is-and that this holiday season, love could be the gift that heals them both. c From dust jackets
Series information from NoveList.
Keywords: Women mayors -- Fiction; Ranches -- Fiction; Texas -- Fiction; Romance fiction